Mantra Batatah di Nagari Lubuak Layang Kecamatan Rao Selatan Kabupaten Pasaman Barat - Noviana, Avinda; Gani, Erizal; Hamidin, Hamidin (Universitas Negeri Padang, 2013)
This study aimed to describe (1) the structure of the text spells batatah, (2) supporting aspects incantations, (3) the process of succession mantra batatah in Nagari Lubuk Rao Elevated Southern District, Pasaman. This research is a qualitative descriptive method. Data collected through the techniques of observation and recording interviews. The study's findings that the structure of the text consists of parts spell batatah opener, the content, and the cover, as well as diction, figurative language (style). Batatah incantations supporting aspects are (a) time: free, (b) the place: in the yard or in the house, (c) events/opportunities: used when the child is eleven months old and above, (d) the perpetrator: the have a mantra that has got inheritance from generation to generation, (e) equipment: seven floral art, black soil, a carpet or rug, yellow rice, bertih, hair oil of lemon, root crops and frankincense, gold ring/dagger/ knife, and water, (f) clothing: free but polite, and (g) means: sitting cross-legged, sit cross-legged and squat. Process in inheritance batatah mantra is to provide the requirements specified by the shaman, in the form of money potluck, knife, blade of steel/a seamstress, a white cloth/ shroud piece.